Study of Extended Spectrum Beta-Lactamases Producing Escherichia Coli and Klebsiella Species in a Tertiary Care Hospital, Biratnagar, Nepal - Yadav, Kumari Ragani; Singh, Ganesh kumar; Bhattacharjee, Sujit; Shrestha, Kewal (Journal of Nobel Medical College, 2019)
Background: Escherichia coli and Klebsiella species are most common ESBL producers and associated with UTI in both community and hospital setting, often limiting the treatment therapy of UTI. Aim of present study was Isolation and Identification of ESBL producing E. coli and Klebsiella Species in urine sample from cases of UTI and their antibiotic susceptibility pattern at Nobel Medical College Teaching Hospital, Biratnagar, Nepal.Materials and Methods: This descriptive cross-sectional study was conducted at Nobel Medical College with effect from October 2018 to June 2019 after approval from the Institutional Review Committee (IRC) of the college as per clinical laboratory standards institute of (CLSI) guidelines.Results: Out of total 2567 urine samples, 631(24.5%) samples showed microbial growth. Among which E. coli was 288(45.6%), Klebsiella species were 20(31.5%), other gram-negative bacteria were 158(25%), gram positive bacteria were 114(18%) and fungus 51(8%) were recovered. Out of 631 culture positive urine samples, 308 urine samples were positive for E. coli/K. species 288(93.5%)/20(42.5%) respectively. Among which ESBL isolates were 213(69%) and non ESBL isolates were 95(31%). All ESBL producing E. coli and K. species were found (100%) sensitive to meropenem. Similarly, among other antibiotics also showed increased susceptibility towards the piperacillin/tazobactum (97.2%),cefoperazone/sulbactum (94.4%) and amikacin (93.0%).Conclusion: The highest numbers of ESBL producers E. coli and K. species from urine sample are increasing day by day and creating serious problem in treating patients in Nepal. So it should be mandatory and very essential to have routine monitoring system to detect the ESBL producing isolates in clinical laboratories.